IMPLEMENTASI METODE REWARD AND PUNISHMENT PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM NUR HIDAYAH BALIKPAPAN - Azrimatul Khumairoh; Ika Ratih Sulistiani; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The research with the title of implementing the reward and punishment method inIslamic religious education subjects at Nur Hidayah Islamic Middle School Balikpapan aims to describe the planning, implementation and results of the implementation of the reward and punishment method at Nur Hidayah Islamic Junior High SchoolBalikpapan. The method used in this research is qualitative research. The results ofthis study are: 1) PAI teachers plan a reward and punishment method that is combinedin lesson plans, syllabus, semester programs, annual programs and academiccalendars to support learning objectives. (2) at the stage of implementing the rewardand punishment method, the teacher gives rewards as a tool education, not as wages.Whereas in giving punishment, the teacher does not directly impose punishment onstudents, but considers it first, resulting in changes in behavior expected by the teacher.3) the benchmark for the success of PAI learning using the reward and punishmentmethod can be seen through three aspects, namely cognitive, affective andpsychomotor.Kata Kunci: metode, reward and punishment, pendidikan agama Islam